[Sculpture of Echo, Café Australia, Melbourne, 3] (1916)
The muse sculptures in Café Australia included Daphne, Echo and Persephone--Source: "The Griffins in Australia and India", p. 137.
Part of the collection: Eric Milton Nicholls collection.
Title devised by cataloguer based on information from Vernon inventory listing and reference sources.
Sculpture by Margaret Baskerville.
Condition: Good.
Also available online
Purchased from Marie and Glynn Nicholls, 2006.
Keywords: Baskerville, Margaret, -- 1861-1930.; Café Australia (Melbourne, Vic.) -- Photographs; Muses (Greek deities) -- Photographs; Sculpture -- Victoria -- Melbourne -- Photographs